2007
DOI: 10.1007/s10350-006-0708-x
|View full text |Cite
|
Sign up to set email alerts
|

Anastomotic Leaks: What is the Best Diagnostic Imaging Study?

Abstract: Early intervention in patients who develop an anastomotic leak can be shown to improve the ultimate outcome, especially with respect to mortality. It is usually necessary to obtain objective tests of anastomotic integrity because of the nonspecificity of clinical signs. Our study supported the superiority of water-soluble enema to CT imaging in patients in whom both modalities were used. This difference was most pronounced for distal anastomotic leaks, whereas no radiologic imaging study proved effective in ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 20 publications
1
65
1
2
Order By: Relevance
“…This observation opens the discussion whether to perform radiographic imaging before relaparotomy. Nicksa et al [16] retrospectively studied 36 patients who were reoperated for anastomotic leakage and found that 3 of the 18 contrast enemas (17%) and 14 of the 27 CT scans (52%) were false-negative. Another study described 16 patients with a clinical anastomotic leakage, in whom four imaging studies (25%) were initially misinterpreted [17] .…”
Section: Discussionmentioning
confidence: 99%
“…This observation opens the discussion whether to perform radiographic imaging before relaparotomy. Nicksa et al [16] retrospectively studied 36 patients who were reoperated for anastomotic leakage and found that 3 of the 18 contrast enemas (17%) and 14 of the 27 CT scans (52%) were false-negative. Another study described 16 patients with a clinical anastomotic leakage, in whom four imaging studies (25%) were initially misinterpreted [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Our review shows that CT with Gastrografin provided the most reliable differential diagnosis between POI and mechanical obstruction (LOE: 1c) [25]. Our previous systematic review regarding the detection of anastomotic leakage also demonstrated it to be a reliable diagnostic tool [41], which may assist the differential diagnosis between POI and septic ileus, due to anastomotic leakage by radiological manifestations such as the existence of extraluminal contrast, perianastomotic air, and fluid collections in the CT scan as adjuvants to the clinical manifestations and laboratory tests [42,43]. These integrated results suggest that CT scan should be recommended when suspicion is aroused.…”
Section: Discussionmentioning
confidence: 99%
“…[12] Besides clinical indicators, many biochemical and radiological tests have been studied with the expectation of timely diagnosis. [13,14] A recent study using CRP as an indicator of anastomotic leakage after colorectal resection showed that higher levels might help to detect the leage before becoming clinically apparent. [15] The detection of cytokines through intraperitoneal microdialysis has also been implicated as a tool for detection of anastomotic leakage prior to the emerging of clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%